The Persistence of Sexual Scripts and Compromised Sexual Agency: A Critical Discourse Analysis of the Songs "Baby It's Cold Outside" and "Blurred Lines". - Greer, Kirsten M.; Cary, Kyla M.; Lester, Jessica Nina; Jozkowski, Kristen N. (Sexuality & Culture, 2025)
Given the lack of formal sexuality education in the United States, adolescents often rely on media, such as music, for information about sexual behavior, including sexual consent. However, popular music lyrics may perpetuate expectations for sexual behavior and consent communication that reflect unequal power between men and women, as well as sexual coercion. In this study, we used critical discourse analysis to examine the lyrics of two popular songs that have sparked public discussion of sexual consent and sexual coercion, "Baby It's Cold Outside" and "Blurred Lines." Grounded in sexual socialization and sexual script theory, we identified three recurring patterns within both songs, including: (1) Traditional Sexual Scripts, (2) Gendered Societal Expectations, and (3) Consent Miscommunication. Guided by our findings, we provide suggestions for educators to combat messages of traditional gendered norms, rape myths, and sexual coercion within music lyrics and incorporate media literacy into sexuality education.